PENGARUH KEGIATAN FINGER PAINTING TERHADAPA KREATIVITS ANAK KELOMPOK B TK DHARMA WANITA 4 MOJODUWUR - Alin Titin Maskhurin; Wijaya Adi Putra; Sarwo Danuji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of finger painting activities on the creativity of group B children at TK D harma Wanita 4 Mojoduwur. The background of this research is the low creativity of children, especiallyin expressing ideas, using colors, and imagination during learning activities. This study uses aquantitative approach with a pre experimental design in the form of a one group pretest-posttest design. the subjek of study weregroup B children at TK Dharm Wanita 4 Mojoduwur. Data colection techniques were carried out througt observasion and children’s creativity increased after the implementasion of finger painting activities. This can be seen from the comparation of pretest and posttest scores, where the posttset result are higher than the pretest. Thus, finger painting activities have a positiv effect on increassing the activity of group B children at TK Dharma Wanita 4 Mojoduwur.